Effects of BYL-719 (alpelisib) on human breast cancer stem cells to overcome drug resistance in human breast cancer - Yu, Leinan; Zang, Chuanbing; Ye, Yuanchun; Liu, Hongyu; Eucker, Jan (Frontiers in Pharmacology, 2024)
Introduction: Breast cancer continues to be a major health concern and is currently the most commonly diagnosed cancer worldwide. Relapse, metastasis, and therapy resistance are major clinical issues that doctors need to address. We believe BYL-719, which is PI3 kinase p110а inhibitor, could also inhibit the breast cancer stem cell phenotype and epithelial-to-mesenchymal transition (EMT). In addition to the PI3K/AKT signaling pathway, BYL-719 can also inhibit essential cancer-related signaling pathways, all of which would ultimately act on the microenvironment of cancer stem cells, which is quite complicated and regulates the characteristics of tumors. These include the stemness and resistance of malignant tumors, plasticity of cancer stem cells, and anti-apoptotic features.A three-dimensional (3D) mammosphere culture method was used in vitro to culture and collect breast cancer stem cells (BCSCs). MTT, clonogenic, and cell apoptosis assays were used to detect cell viability, self-renewal, and differentiation abilities. A sphere formation assay under 3D conditions was used to detect the mammophore inhibition rate of BYL-719. The subpopulation of CD44 + CD24 -was detected using flow cytometry analysis while EMT biomarkers and essential signaling pathways were detected using western blotting. All the data were analyzed using GraphPad Prism 9 software. Results: BCSC-like cells were obtained by using the 3D cell culture method in vitro. We confirmed that BYL-719 could inhibit BCSC-like cell proliferation in 3D cultures and that the stemness characteristics of BCSC-like cells were inhibited. The PI3K/AKT/mTOR signaling pathway could be inhibited by BYL-719, and the Notch, JAK-STAT and MAPK/ERK signaling pathways which have crosstalk in the tumor microenvironment (TME) are also inhibited. By comparing eribulin-resistant breast cancer cell lines, we confirmed that BYL-719 could effectively overcome drug resistance.Summary/conclusions: The 3D cell culture is a novel and highly effective method for enriching BCSCs in vitro. Furthermore, the stemness and EMT of BCSCs were inhibited by BYL-719 by acting on various signaling pathways. Finally, we believe that drug resistance can be overcome by targeting the BCSCs. Conjugation of BYL-719 with other anti-neoplastic agents may be a promising treatment for this in clinic.